Eficiência da cokrigagem na estimativa da produtividade do café conilon - Quartzani, Waylson Zancanella [UNESP]; Zimback, Celia Regina Lopes [UNESP]; Landim, Paulo Milton Barbosa [UNESP]; Oliveira, Rone Batista de [UNESP] (EIA Energy in Agriculture, 2011)
The objective of this research was to estimate the productivity (PRODUT) in sc/ha of coffee conilon through the technique of cokriging, using as covariate the production of humid coffee (PROD) in kg and compare the results with estimates obtained by kriging ordinary. The study was conducted in a commercial area of conilon coffee, Coffea canephora Pierre var. conilon, located in São Mateus Municipality, Espirito Santo State. For the field work was sampled the humid coffee production in a sampling grid irregular of 18.5 ha, 87 sampling points in the total. We also determined the production of dry coffee beans and coffee benefited 12% moisture, to obtain the PRODUT variable. After exploratory data analysis, which showed the correlation between variables in the order of 0.899, was performed variogram analysis. Were adjusted theoretical variograms to PROD and PRODUT and cross variogram between two variables. Finally we estimated the value of productivity, both by ordinary kriging as per cokriging. The validation of the estimation by cokriging not shows, however, significant gains in relation to validation by ordinary kriging.

O objetivo do trabalho foi estimar a produtividade (PRODUT) em sc/ha do café conilon por meio da técnica de cokrigagem, usando como covariável a produção de café úmido (PROD) em kg e comparar o resultado com a estimativa obtida por krigagem ordinária. O estudo foi realizado em uma área comercial de café conilon, Coffea canephora Pierre, Var. conilon, localizada no Município de São Mateus-Espirito Santo. Para o trabalho foi amostrada em campo a produção de café úmido numa malha amostral irregular de 18,5 ha, totalizando 87 pontos amostrais. Foram determinados também, a produção de café seco e café pilado a 12% de umidade, para obtenção da variável PRODUT. Após a análise exploratória dos dados, que mostrou a correlação entre as variáveis da ordem de 0,899, foi efetuada a análise variográfica. Foram ajustados variogramas teóricos para PROD e PRODUT e variograma cruzado entre as duas variáveis. Finalmente foram estimados os valores para PRODUT, tanto por krigagem ordinária como por cokrigagem. A validação da estimativa por cokrigagem não mostrou, porém, ganhos significativos em relação à validação por krigagem ordinária.
Efficiency of cokriging to estimate coffee conilon productivity
Keywords: Cross-variogram; Kriging; Coffea canephora; Variograma cruzado; Kigagem; Coffea canephora